Flow field analysis around pressure shielding structures - Szoke, Máté; Hari, Nandita Nurani; Devenport, William J.; Glegg, Stewart A.; Teschner, Tom-Robin (Cranfield University, 2021)
The flow field around a series of streamwise rods, referred to as canopies, is investigated using two-dimensional two-component time-resolved particle image velocimetry (PIV) and large eddy simulations (LES) to characterize the changes in the flow field responsible for reducing the low and high-frequency surface pressure fluctuations previously observed. It was found that an axisymmetric turbulent boundary layer (ATBL) develops over the rods, whose thickness grows at a greater rate above the rods than below. This boundary layer reaches the wall below the rods at a point where previously a saturation was found in the low-frequency noise attenuation, revealing that the ATBL is responsible for the low-frequency noise attenuation. The flow is displaced by the presence of the rods, particularly above them, which offset was primarily caused by the blockage of the ATBL. The flow below the rods exhibits the properties of a turbulent boundary layer as its profile still conforms to the logarithmic layer, but the friction velocity was found to drop. This viscous effect was found to be responsible for the high-frequency noise attenuation reported previously.